SILENCE AS PARTICIPATION? STUDENT VOICES ON CULTURAL IDENTITY IN INTERCULTURAL CLASSROOM COMMUNICATION - Anugerah Febrian Syam; Areski Wahid; Andi Hudriati (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Studies on classroom silence have often explained student position through the perspectives of communication anxiety, linguistic limitations, or low participation. Readings that position silence as a culturally negotiated communication practice in intercultural classroom communication are still relatively limited. This study aims to explore how students interpret silence and how cultural identity shapes their participation in cross-cultural classroom interactions. This study used a Classroom Ethnography approach, involving 22 students in a single college class, with 10 focal participants for in-depth exploration. Data were collected through classroom observations, field notes, audio-video recordings, stimulated recall interviews, ethnographic interviews, and student reflective narratives. Data were analyzed using iterative interpretive analysis through the identification of critical interactional episodes, ethnographic coding, constant comparative analysis, and the development of ethnographic themes. The findings indicate that silence functions as face protection, linguistic self-monitoring, hierarchical navigation, cultural discipline, and selective participation. This study concludes that silence is not an absence of participation, but rather a culturally negotiated participation that reflects the negotiation of identity, social risks, and communication norms in academic spaces.